Revised phylogeny of mouflon based on expanded sampling of mitogenomes - Paolo Mereu; Monica Pirastru; Pedro Morell Miranda; Gözde Atağ; Kıvılcım Başak Vural; Barbara Wilkens; André Elias Rodrigues Soares; Damla Kaptan; Marco Zedda; Nicolò Columbano; Mario Barbato; Salvatore Naitana; et al. (PLoS ONE, 2025)
Mouflons are flagship species of the Mediterranean islands where they persist. Once thought to be the remnants of a European wild sheep population, archaeology suggests they were introduced by humans to the islands of Cyprus in the Early Neolithic (~10,000 years ago) and later to Corsica and Sardinia. Their status as truly wild animals remains a subject of debate. To investigate the phylogenetic relationship between these island populations and other domestic and wild sheep from the Mediterranean region, we sequenced 50 mitogenomes of mouflons from Sardinia and Corsica, and modern and ancient Sardinian domestic sheep. A total of 68 additional publicly available mitogenomes were included in the comparative analysis and used to reconstruct the phylogeny of sheep and its closest wild relative, the mouflon (Ovis gmelini). Our study analyzed the evolutionary relationships within the C-E-X and haplogroup B clusters, showing that: a) Cyprus mouflons are more related to Anatolian and Iranian mouflons belonging to the wild haplogroup X, which seems to be basal to the domestic C and E haplogroups; b) Corsican and Sardinian mouflon arise from basal lineages associated with the early European expansion of domestic sheep. These results highlight the phylogenetic distinctiveness of the mouflon populations from the Mediterranean islands, suggesting a revision of their systematic classification and an update of the nomenclature for Sardinian and Corsican mouflons from the current status of subspecies of domestic sheep (Ovis aries musimon) to subspecies of their wild relatives (Ovis gmelini musimon) which would facilitate conservation efforts.